How Psychological Barriers Constrain Men’s Interest in Gender-Atypical Jobs and Facilitate Occupational Segregation - Suh, Eileen Y.; Apfelbaum, Evan P.; Norton, Michael I. (Organization Science, 2025)
Scholarship regarding occupational gender segregation has almost exclusively focused on women’s experiences (e.g., as targets of discrimination in masculine domains), yet understanding factors that perpetuate men’s underrepresentation in traditionally feminine occupations is equally important. We examine a consequential dynamic early in the job search process in which individuals come to learn that an occupation that fits them is perceived as feminine versus masculine. Our research develops and tests the prediction that femininity or masculinity of occupations will exert a stronger impact on men’s (versus women’s) interest in them such that men will be less interested in gender-atypical occupations than women. Across five studies (n = 4,477), we consistently observed robust evidence for this prediction among diverse samples, including high school students (Study 1), unemployed job seekers (Study 2), U.S. adults (Study 3), and undergraduates (Study 4) and using experimental and archival methods. We observed this asymmetry after controlling for alternative accounts related to economic factors (e.g., expected salary), suggesting that they alone cannot fully explain men’s lack of interest in feminine occupations as previously discussed in the literature. Further, we consistently observed that men, compared with women, show heightened sensitivity to gender-based occupational status, and this greater sensitivity explains men’s (versus women’s) reduced interest in gender-atypical occupations. Though past scholarship suggests that increasing pay is key to stoking men’s interest in feminine occupations, our research suggests that targeting men’s underlying psychological concern—sensitivity to gender-based occupational status—may be an underappreciated pathway to reducing gender segregation. Supplemental Material: The data, materials, preregistration, and ancillary analyses for all studies are available at https://osf.io/h4mgx/?view_only=9a4dbfc9d122417c880354d6b3462072 and at https://doi.org/10.1287/orsc.2023.17550 .